Aspergillus awamori MH2 as a novel maltobionic acid producer: production optimization and application - Soad M. Yehia; Yousseria M. Shetaia; Ghoson M. Daba; Faten A. Mostafa; Ali A. Ali; Hassaan El-Menoufy (Microbial Cell Factories)
Abstract Background Producing bio-based chemicals using a straightforward and ecologically responsible biotechnological method is intriguing. Maltobionic acid (MBA) is an aldobionic acid obtained from maltose oxidation and is an industrially applied compound. Having antioxidative and antimicrobial, non-toxic, highly water soluble, moisturizing, metal chelating, mildly sour and slightly sweet characteristics. Results This study succeeded in utilizing Aspergillus awamori as a novel MBA producer. MBA production was improved through two-step statistical factorial designs. Plackett-Burman Design (PBD) investigating the qualitative interaction between eleven factors (maltose, KNO3, NaCl, KH2PO4, K2HPO4, MgSO4, FeSO4.7H2O, initial pH, temperature, incubation time and rpm) on MBA production causing 1.37- fold increase. Central Composite design (CCD) analyzing the quantitative interaction between the most MBA production affecting factors (temperature, rpm, KH2PO4, and incubation period) gave a 1.64- improvement in MBA production compared with un-optimized medium. The addition of agro-industrial wastes (AIW) (corn cobs and artichoke leaves) to optimized medium g/l (maltose, 5; KNO3, 1; KH2PO4, 1.0; MgSO4, 0.5; FeSO4.7(H2O), 0.02; pH, 5.00 at 37.5 °C for 9.5 days at 125 rpm) caused 2.41- and 1.97- fold increase in MBA production, respectively in comparison with the initial production conditions. MBA produced by A. awamori MH2 exerted an anti-oxidant activity with a ratio of 86% using DPPH scavenging assay.